2015
DOI: 10.2500/ajra.2015.29.4212
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Culturally Modified University of Pennsylvania Smell Identification Test for a Turkish Population

Abstract: The UPSIT-T modification is an adequate olfactory test for clinical use in a Turkish population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 25 publications
0
20
0
2
Order By: Relevance
“…At last 24 articles were included (see selection flowchart in Figure 1). The studies (16,19,20,28,(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58) included for each of the three groups are shown in Table 1. Table 1 showed the demographic characteristics of participants and measures used in odor identification.…”
Section: Resultsmentioning
confidence: 99%
“…At last 24 articles were included (see selection flowchart in Figure 1). The studies (16,19,20,28,(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58) included for each of the three groups are shown in Table 1. Table 1 showed the demographic characteristics of participants and measures used in odor identification.…”
Section: Resultsmentioning
confidence: 99%
“…Since odor disorder is a subjective concept, objective tests were needed in its diagnosis. There are two types of odor [10,15,35]. These tests can also be used in the diagnosis of olfactory disorders in COVID-19 .…”
Section: Discussionmentioning
confidence: 99%
“…In our study, patients who had olfactor loss in COVID-19 were tested both for smell and the olfactory regions were examined by taking Paranasal Sinus Tomography (CT). The most frequently used scent tests are "The University of Pennsylvania Smell Identi cation Test (UPSIT)", "Connecticut (CCCRC) Olfactory Test", "Sni n 'Sticks" Olfactory Test " [15][16][17]. In our study, we used the Connecticut (CCCRC) Olfactory Test, which is easy and fast to apply, and we tried to elucidate the pathophysiology of COVID-19 olfactory disorder by comparing the degrees of odor disorder and radiological ndings.…”
Section: Introductionmentioning
confidence: 99%
“…The technique's success rate was 92.8% and resulted in improved olfactory function scores 1, 3, and 6 months after the procedure. 12 The second article on olfactory dysfunction is by Altundag et al 13 who developed a cross-cultural adaptation of the University of Pennsylvania Smell Identification Test (UPSIT) and investigated its applicability in 51 healthy Turkish subjects. The modified version increased the identification rates of test odorants, which indicated that the UPSIT-T modification is a reliable tool for clinical use in a Turkish population.…”
Section: T His Issue Of American Journal Of Rhinology Andmentioning
confidence: 99%
“…The modified version increased the identification rates of test odorants, which indicated that the UPSIT-T modification is a reliable tool for clinical use in a Turkish population. 13 Olfactory loss is a reported complication after transnasal endoscopic pituitary surgery. Chaaban et al 14 followed up 18 patients who underwent endoscopic transnasal pituitary surgery.…”
Section: T His Issue Of American Journal Of Rhinology Andmentioning
confidence: 99%